Evaluating the Implementation of a Mental Health Referral Service “Connect to Wellbeing”: A Quality Improvement Approach - Onnis, Leigh-ann; Kinchin, Irina; Pryce, Josephine; Ennals, Priscilla; Petrucci, Joe; Tsey, Komla (Frontiers in Public Health, 2020)
This article presents the findings from a study that evaluated the process of implementing Connect to Wellbeing (CTW), a new mental health intake, assessment and referral service in regional Australia, to determine how well it connected the right person, to the right service, at the right time. The study used the CTW experience to better understand: the process of implementing CTW; the barriers and factors enabling implementation of CTW; and to identify outcome measures suitable for ascertaining both the effectiveness of CTW in client health outcomes, and conducting a value for money analysis. The process evaluation found that CTW had improved processes, removed waitlists and broadened the scope and type of psychological services offered which enabled more timely connection of people to psychological services. Therefore, despite some barriers, the enablers were such that CTW adapted to the environment, and improved the process of connecting people with the right services. Potential outcome measures were assessed; however, limitations such as missing data, led to inconclusive findings. The assessment of potential outcome measures provided insight into suitable measures and it is recommended that CTW continue collecting the data, as part of routine data collection into the future.